Vernalization shapes shoot architecture and ensures the maintenance of dormant buds in the perennial Arabis alpina. Issue 1 (12th March 2020) - Vayssières, Alice; Mishra, Priyanka; Roggen, Adrian; Neumann, Ulla; Ljung, Karin; Albani, Maria C.
Summary: Perennials have a complex shoot architecture with axillary meristems organized in zones of differential bud activity and fate. This includes zones of buds maintained dormant for multiple seasons and used as reservoirs for potential growth in case of damage. The shoot of Arabis alpina, a perennial relative of Arabidopsis thaliana, consists of a zone of dormant buds placed between subapical vegetative and basal flowering branches. This shoot architecture is shaped after exposure to prolonged cold, required for flowering. To understand how vernalization ensures the maintenance of dormant buds, we performed physiological and transcriptome studies, followed the spatiotemporal changes of auxin, and generated transgenic plants. Our results demonstrate that the complex shoot architecture in A. alpina is shaped by its flowering behavior, specifically the initiation of inflorescences during cold treatment and rapid flowering after subsequent exposure to growth‐promoting conditions. Dormant buds are already formed before cold treatment. However, dormancy in these buds is enhanced during, and stably maintained after, vernalization by a BRC1‐dependent mechanism. Post‐vernalization, stable maintenance of dormant buds is correlated with increased auxin response, transport, and endogenous indole‐3‐acetic acid levels in the stem. Here, we provide a functional link between flowering and the maintenance of dormant buds in perennials.